Mathematical Critical Thinking Ability in Solving Mathematical Problems - Anisa Nurfadilah Nurdin; Rusli; Baso Intang Sappaile; Hastuty; Sitti Masyitah Meliyana R. (ARRUS Journal of Social Sciences and Humanities, 2022)
This study aims to determine the mathematical critical thinking skills of class XII IPA 1 students at SMAN 5 Sidrap in solving mathematical problems in arithmetic sequences and series. The type of research used is descriptive research with a qualitative approach. In this study, there were 3 subjects, namely students with high, medium and low mathematical abilities. The instruments used in data collection were observation sheets, written tests and interview guidelines. The results showed that: (1) Students who met the Critical Thinking Level (CTL) 3 or critically were students who had high mathematical abilities. At this critical thinking level, students are able to formulate the main points of the problem, are able to reveal existing facts, are able to determine the theorems used and detect bias, Students are able to work on questions according to the initial plan, able to express their arguments clearly, able to re-examine answers and draw conclusions. (2) Students who meet CTL 2 or are quite critical are students who have moderate mathematical abilities. At this critical thinking level, students are able to formulate the main points of the problem, uncover existing facts, are able to determine the theorem used, are able to detect bias, are able to work on problems according to the initial plan, are able to express their arguments clearly, are less able to re-examine answers and draw a conclusion. (3) Students who meet CTL 0 or are not critical are students who have low mathematical abilities. At this critical thinking level, students have not been able to fulfill all indicators such as not being able to formulate the main points of the problem.